Ability to Identify Persuasive Sentences in Negotiation Texts Using Learning Models Cooperative Integrated Reading And Composition (CIRC) Class X Students of SMK Negeri 1 Batang Angkola - Aritonang, Devinna Riskiana (Jurnal Hata Poda, 2024)
This research is entitled "Identifying Persuasive Sentences in Negotiation Texts Using Learning Models Cooperative Integrated Reading and Composition (CIRC) Class X Students of SMK N 1 Batang Angkola”. The aim of this research is to describe the ability to identify persuasive sentences in negotiation texts using a learning model Kooperatif Integrated Reading and Composition (CIRC) students. This research method uses quantitative methods with a descriptive approach. The population in this study were all class X students at SMK Negeri 1 Batang Angkola, totaling 279 students. The sample used in this research was 36 students of class random sampling. The data collection technique uses 10 multiple choice questions and 5 fill-in-the-blank questions. The research results show differences in the average scores for variables X and Y. The average score for variable After the data is analyzed it can be stated that N=36 with X= 2920, Y= 2655,2= 243000, AND2= 200825, so XY = 218000. Then looking at the average, it can be shown that X= 81.11, Y= 73.752= 6750, AND2= 5578.47 XY = 6055.5. This is based on hypothesis testing carried out on the data found, namely the hypothesis obtained that the rxy value is 0.477 so that when compared with the r table, namely (0.477 0.339), the hypothesis in this study is accepted.Keywords: Persuasive Sentences, Negotiation Texts, CIRC Learning.